Comparative calibrations of measuring microphones performed in a free field - Wszołek, Grażyna; Barwicz, Wiesław (Archives of Acoustics, 2007)
Comparison of calibrations of measuring microphones obtained in two laboratories – Laboratory of Physikalisch-Technische Bundesanstalt in Braunschweig (Germany) and Laboratory of Vibroacoustics at the University of Science and Technology in Kraków (Poland) is presented in the paper. However, the performed calibrations were not the official Inter-Laboratory Comparisons (ILC), since those comparisons in the field of Calibrations of reference microphones in a free field are still at the preparatory stage. The paper contains comparisons of the calibration results (together with uncertainty of measurements) obtained in both laboratories for exactly the same devices as well as the traceability of the results. According to the guidelines of the Polish Centre for Accreditation – given in the DA-05 document – the index E_n constitutes the assessment criterion. The selected problems related to calibrations and influencing their results – are discussed by the authors. They have drawn a special attention to comparisons of the calibration results obtained in various laboratories. Those problems are connected – among others – with the lack of basic data in the Calibration Certificates concerning e.g. traceability of the results, reference microphones, methods of measurements and uncertainty of measurements assessments. The paper contains suggestions concerning further co-operation of laboratories in this field.